2017
DOI: 10.4103/2224-3151.206170
|View full text |Cite
|
Sign up to set email alerts
|

Motivating and demotivating factors for community health workers: A qualitative study in urban slums of Delhi, India

Abstract: Background Community health workers play an important role in delivering health-care services, especially to underserved populations in low- and middle-income countries. They have been shown to be successful in providing a range of preventive, promotive and curative services. This qualitative study investigated the factors motivating or demotivating community health workers in urban settings in Delhi, India. Methods In this sub-study of the ANCHUL (Ante Natal and Child Healthcare in Urban Slums) implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 2 publications
11
57
0
Order By: Relevance
“…Measures like nancial incentives, structured reporting patterns, assignment of clear roles and responsibilities, have to be introduced before for CHWs to accept the role of OHAs. Evidence indicates the importance of social recognition [43,44] and fair monetary incentives [34,45] for FHWs, which was also re ected in both the quantitative and qualitative ndings of this study. A multi-stakeholder perspective study on the work performance of ASHAs by Sharma et al [46] documented professional factors such as training and job security strengthening that would improve their performance, which was also documented in the health system level qualitative ndings of this study.…”
Section: Discussionsupporting
confidence: 72%
“…Measures like nancial incentives, structured reporting patterns, assignment of clear roles and responsibilities, have to be introduced before for CHWs to accept the role of OHAs. Evidence indicates the importance of social recognition [43,44] and fair monetary incentives [34,45] for FHWs, which was also re ected in both the quantitative and qualitative ndings of this study. A multi-stakeholder perspective study on the work performance of ASHAs by Sharma et al [46] documented professional factors such as training and job security strengthening that would improve their performance, which was also documented in the health system level qualitative ndings of this study.…”
Section: Discussionsupporting
confidence: 72%
“…22,24 The many problems experienced by CHWs because of their position at the bottom of the health system hierarchy, and because of the unequal gender power relations between the generally female CHWs and other health cadres and society, have been well documented, 23 including in India. 19,20,28,29 These issues are important and are material to our study context too -they need to be systematically and thoroughly addressed at the policy-practice level. Our study however sheds light on a hitherto under-reported aspect of being a CHW.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the lack of recognition of CHWs in MoH programmes has been cited as a challenge (20,40,41,45,46). Increased recognition is seen as potentially improving lay health worker performance (43).…”
Section: Recommendationsmentioning
confidence: 99%